2023
DOI: 10.1186/s12913-023-09378-8
|View full text |Cite
|
Sign up to set email alerts
|

Safe acceptance in the nurses’ cultural care of medical tourists in Iran: a qualitative study

Abstract: Background Medical tourism is traveling to another country to promote, restore and maintain health, recreation, and pleasure. There are different types of health tourism, including medical tourism, recovery tourism, and preventive tourism. This study aimed to explain safe acceptance in the nurses’ cultural care of medical tourists in Iran. Methods In this qualitative study, 18 semi-structured interviews were conducted with nurses, patients, and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…this was similarly claimed in two studies by Zia Sheikholeslami et al 24,25 Moreover, in our study, high quality and low price of services, positive international image of the destination country, and the ability to treat a specific type of disease were the most important factors in attracting foreign patients from the student's point of view, which was reported in two studies by Zia Sheikholeslami et al 24,25 A study by Hamzehpour et Interacting with international patients can broaden their knowledge and understanding of different healthcare practices. 38 In this regard, our study revealed that almost half of the subjects did not have any idea about whether the development of health tourism could lead to the improvement of the level of medical knowledge of medical professionals or not, while the studies carried out by Zia Sheikholeslami et al 24,25 demonstrated that the majority of participants believed that the entry of health tourists might cause the development of Iranian physicians' knowledge. Regarding this attitude, a literature review on health tourism by Zhong et al…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…this was similarly claimed in two studies by Zia Sheikholeslami et al 24,25 Moreover, in our study, high quality and low price of services, positive international image of the destination country, and the ability to treat a specific type of disease were the most important factors in attracting foreign patients from the student's point of view, which was reported in two studies by Zia Sheikholeslami et al 24,25 A study by Hamzehpour et Interacting with international patients can broaden their knowledge and understanding of different healthcare practices. 38 In this regard, our study revealed that almost half of the subjects did not have any idea about whether the development of health tourism could lead to the improvement of the level of medical knowledge of medical professionals or not, while the studies carried out by Zia Sheikholeslami et al 24,25 demonstrated that the majority of participants believed that the entry of health tourists might cause the development of Iranian physicians' knowledge. Regarding this attitude, a literature review on health tourism by Zhong et al…”
Section: Discussionmentioning
confidence: 59%
“…Interacting with international patients can broaden their knowledge and understanding of different healthcare practices. 38 In this regard, our study revealed that almost half of the subjects did not have any idea about whether the development of health tourism could lead to the improvement of the level of medical knowledge of medical professionals or not, while the studies carried out by Zia Sheikholeslami et al 24 , 25 demonstrated that the majority of participants believed that the entry of health tourists might cause the development of Iranian physicians' knowledge. Regarding this attitude, a literature review on health tourism by Zhong et al revealed that the rise of medical‐health‐wellness tourism emphasizes the privatization of healthcare, an increasing dependence on technology, and the accelerating globalization of healthcare and tourism.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation